TEMPERATURE CONTROL SYSTEM AND FABRICATION METHOD THEREOF - MIOW, Kit Fong (2016)
Embodiments of the invention relate to a temperature control system and fabrication method thereof. The temperature control system includes an ice pool configured to control air temperature of a given space above a ground surface, the ice pool being recessed in a ground material below the ground surface and includes a multi-layer structure, wherein the multi-layer structure includes in sequence inwardly from exterior of the multi-layer structure: a concrete base layer which provides a casing to the multi-layer structure, a cement sand plaster layer, a first waterproof layer, a thermal insulation layer, a second waterproof layer, a dry sand layer, and a concrete top layer to provide a receptacle for retaining water and ice formed by freezing the water, the concrete top layer having a plurality of refrigeration pipes disposed to freeze the water in the receptacle and control temperature in the receptacle. L'invention concerne, selon des modes de réalisation, un système de régulation de température et un procédé de fabrication correspondant. Le système de régulation de température comprend un bain de glace configuré pour réguler une température d'air d'un espace donné au-dessus d'une surface de sol, la réserve de glace étant en retrait dans une matière de sol au-dessous de la surface de sol, et comprend une structure multicouche, la structure multicouche comprenant en séquence, vers l'intérieur depuis l'extérieur de la structure multicouche : une couche de base en béton qui fournit un logement à la structure multicouche, une couche de plâtre de sable de ciment, une première couche imperméable à l'eau, une couche d'isolation thermique, une seconde couche imperméable à l'eau, une couche de sable sec, et une couche supérieure en béton pour fournir un réceptacle afin de retenir l'eau et la glace formée par congélation de l'eau, la couche supérieure en béton comprenant une pluralité de tuyaux de réfrigération disposés de façon à congeler l'eau dans le réceptacle et réguler une température dans le réceptacle.